1993
DOI: 10.1093/carcin/14.1.79
|View full text |Cite
|
Sign up to set email alerts
|

Effects of risk-associated human dietary macrocomponents on processes related to carcinogenesis in human-flora-associated (HFA) rats

Abstract: Dietary fat, protein and fibre have been shown to modulate cancer risk in humans and the present study examined the biological effects in human-flora-associated (HFA) rats of altering intake levels within the normal human range. Two control groups, one HFA and the other germfree (GF), consumed a human diet low in fat, fibre and beef for 4 weeks; three other groups consumed human diets similar except for independent 3-fold increases in fat, beef protein or fibre. After 2 weeks on the diets, magnetically recover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 0 publications
0
16
0
1
Order By: Relevance
“…This bacterium is thought to reside in the tonsils, from whence it can set up bacteraemia and meningitis; thus this pathology can hardly be associated with intestinal disorders. There is an ample debate about the role of fiber in preventing the development of pathogenic bacteria, in reducing the intestine inflammatory status, in protecting the integrity of the intestinal mucosa and in improving the host immune system (Rumney et al, 1993;Mao et al, 1996;Mathew et al, 1996;Zunft et al, 1997;Wachtershauser and Stein, 2000;Williams et al, 2001). This explorative experiment failed to find a clear evidence of alterations of DNA adducts and of the inflammatory status of the rectum mucosa of sample subjects due to the dietary treatment.…”
Section: Health Statusmentioning
confidence: 95%
“…This bacterium is thought to reside in the tonsils, from whence it can set up bacteraemia and meningitis; thus this pathology can hardly be associated with intestinal disorders. There is an ample debate about the role of fiber in preventing the development of pathogenic bacteria, in reducing the intestine inflammatory status, in protecting the integrity of the intestinal mucosa and in improving the host immune system (Rumney et al, 1993;Mao et al, 1996;Mathew et al, 1996;Zunft et al, 1997;Wachtershauser and Stein, 2000;Williams et al, 2001). This explorative experiment failed to find a clear evidence of alterations of DNA adducts and of the inflammatory status of the rectum mucosa of sample subjects due to the dietary treatment.…”
Section: Health Statusmentioning
confidence: 95%
“…Attachment and overgrowth of the pathogens generally results in acute diarrhoeal infections, however more chronic forms of intestinal disease also occur (Gibson et al, 1997;Gionchetti et al, 2000). These include inflammatory bowel diseases (ulcerative colitis and Crohn's disease) (Chadwick and Anderson, 1995), colon cancer (Rowland, 1988;Rumney et al, 1993) and pseudomembranous colitis (Duerden et al, 1995). To varying extents, each has been linked into microflora composition and activities, and thereby diet as this provides the major source for their growth.…”
Section: The Human Gastrointestinal Tract and Its Microfloramentioning
confidence: 99%
“…As they noted, most of the information on this phenomena was derived from animal work and some human studies and that evidence from a wide range of sources supported the view that the colonic microflora was involved in the etiology of local cancers. Among the major categorizations of evidence, it was indicated that: intestinal bacteria can produce, from dietary components, substances with genotoxic, carcinogenic, and tumor-promoting activities ; gut bacteria can activate pro-carcinogens to DNA-reactive forms; germ-free (GF) rats fed 1,2-dimethylhydrazine or fed human diets had a lower incidence of, respectively, colon tumors and of DNA adducts than similarly-treated rats with a normal microflora Rumney et al, 1993); and, that human fecal matter has been documented to contain mutagenic and genotoxic substances of bacterial origin (Venturi et al, 1997). Moreover, a direct effect of Enterococcus faecalis as an inducer of aneuploidy and tetraploidy was demonstrated in intestinal cell cultures (Wang et al, 2008).…”
Section: Effects Of Intestinal Microbial Environment On Cancer and Namentioning
confidence: 99%